Lecithin‐acrylamido‐2‐methylpropane sulfonate based crosslinked phospholipid nanoparticles as drug carrier. Issue 42 (19th July 2016) - Mutlu, Esra Cansever; Bostan, Muge Sennaroglu; Bahadori, Fatemeh; Kocyigit, Abdurrahim; Oner, Ebru Toksoy; Eroglu, Mehmet S.
ABSTRACT: In this study, a novel paclitaxel (PTX) loaded and a crosslinked solid phospholipid nanoparticles (SLN‐PTX) with negative surface charge was prepared by UV polymerization for drug delivery. Capping of positive charge of zwitterionic lecithin with negative charge of sodium 2‐acrylamido‐2‐methyl‐1‐propanesulfonate (AMPS‐Na) through cation exchange interaction produced a lecithin‐AMPS (L‐AMPS) complex. The amphiphilic and negative charged lipid complex was emulsified in the presence of emulsifier, paclitaxel, initiator, and methacrylated poly ε‐caprolacton‐diol (PCL‐MAC) as a spacer. The colloidal system was subjected to UV‐irradiation to obtain crosslinked nanoparticles. Completion of the UV‐polymerization was monitored with differential scanning calorimetry (DSC), which indicated the disappearance of exothermic peaks of vinyl groups. The nanoparticle system, having an average size of 200 nm, exhibited high drug encapsulation (96%) with negatively charged surface (zeta potential had an average of −70 mV). PTX release profiles of the crosslinked and uncrosslinked SLN‐PTXs were studied and their pharmacological properties were compared. The crosslinked nanoparticles exhibited more controlled release behavior with longer release time compared to the uncrosslinked ones. In vitro cytotoxicity test was conducted on MCF‐7 human breast adenocarcinoma cell line, which indicated that the crosslinked SLN‐PTXs have a potential therapeutic effect for breast cancer treatments. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 44105. Abstract :